2017
DOI: 10.1093/infdis/jix354
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Tuberculosis Transmission

Abstract: Measuring tuberculosis transmission is exceedingly difficult, given the remarkable variability in the timing of clinical disease after Mycobacterium tuberculosis infection; incident disease can result from either a recent (ie, weeks to months) or a remote (ie, several years to decades) infection event. Although we cannot identify with certainty the timing and location of tuberculosis transmission for individuals, approaches for estimating the individual probability of recent transmission and for estimating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
128
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(135 citation statements)
references
References 101 publications
2
128
0
5
Order By: Relevance
“…This figure is similar to that reported from a meta-analysis of ten studies which yielded an estimate of 14.1% (95% confidence interval, 11.6%-16.3%) for the PAF for household transmission [33]. This relatively low figure reflects the fact that tuberculosis disease affects less than 1% of households at any time, even in high incidence settings, making exposure opportunities between a person with tuberculosis and their social network outside the household more numerous [34]. Studies in South Africa have indicated that significant transmission occurs in public transportation [35] and in schools [36].…”
Section: Discussionsupporting
confidence: 82%
“…This figure is similar to that reported from a meta-analysis of ten studies which yielded an estimate of 14.1% (95% confidence interval, 11.6%-16.3%) for the PAF for household transmission [33]. This relatively low figure reflects the fact that tuberculosis disease affects less than 1% of households at any time, even in high incidence settings, making exposure opportunities between a person with tuberculosis and their social network outside the household more numerous [34]. Studies in South Africa have indicated that significant transmission occurs in public transportation [35] and in schools [36].…”
Section: Discussionsupporting
confidence: 82%
“…Although one fourth of the global population is estimated to be latently infected (2), none of the current immunodiagnostics can discriminate between recent and past Mtb infection, or predict risk of possible TB progression in LTBI (3)(4)(5). Although neonatal vaccination with Bacillus Calmette-Guérin (BCG), the only licensed TB vaccine, protects infants against severe forms of TB, it is unable to prevent active pulmonary TB in adults and adolescents, such that it has little impact on Mtb transmission (6). To boost or replace BCG, multiple TB vaccine candidates have been proposed and are being evaluated in different higher end preclinical or clinical phase 1 and phase 2 studies (7).…”
mentioning
confidence: 99%
“…Although the dataset used was relatively small, these findings add to the current limited literature on the topic. 4446 Overall our study highlights the utility of WGS in resolving transmission links particularly in high burden settings where several transmission chains may occur simultaneously. WGS of a well characterized cluster through MIRU-VNTR led to identification of several sub-clusters with further granularity achieved from addition of variants in regions that are routinely excluded from these analyses.…”
Section: Discussionmentioning
confidence: 67%